Wenjing Zhitong Decoction Alleviates Primary Dysmenorrhea Mediated by Pain Sensitization Via the ERα‐BDNF Signaling Pathway. - Qin, Yajie; Yang, Xiaotian; Tang, Xingran; Zhao, Huijin; Zhou, Huifang; Chauhan, Anjali (Journal of Clinical Pharmacy & Therapeutics, 2025)
Background: Wen‐Jing‐Zhi‐Tong decoction (WJZTD) is a traditional Chinese medicine herbal decoction that has demonstrated clinical efficacy in treating primary dysmenorrhea (PDM) over decades. However, the underlying therapeutic mechanism of WJZTD requires further clarification. Objective: This study aims to explore and elucidate the therapeutic mechanism of WJZTD in treating PDM through metabolomics, integrated network pharmacology, as well as in vitro and in vivo experiments. Methods: A PDM rat model was established by estradiol benzoate and oxytocin for 3 consecutive estrous cycles, and then WJZTD treatment was administered for 3 consecutive estrous cycles. To evaluate the therapeutic effect of WJZTD on PDM, behavioral tests, histological analysis, and evaluation of serum prostaglandins (PGs) were performed. Moreover, immunofluorescence and Western blot analysis were carried out in dorsal root ganglion (DRG) tissues to explore the role of WJZTD in reducing pain sensitivity. Metabolomics and integrated pharmacology were utilized to identify potential bioactive targets, which were then validated through in vitro experiments. Results: WJZTD significantly reduces pain sensitivity in PDM rats, treating the condition effectively by decreasing brain‐derived neurotrophic factor (BDNF) protein expression, c‐Fos‐positive neurons in DRG, and serum prostaglandin PGF2α (PGF2α) levels. A nontargeted metabolic analysis identified 11 differential metabolites, suggesting ESR1 (estrogen receptor α, ERα) as a potential target. In vitro experiments confirmed WJZTD's efficacy in treating PDM through regulating the ERα/BDNF signaling pathway. Conclusion: WJZTD decreases the excitability of DRG neurons in rats with PDM through the ERα/BDNF pathway, which enhances pain sensitization and contributes to reducing dysmenorrhea.